Effects of Fluorine and BaO on the Crystallization Behavior of Lime–Alumina-Based Mold Flux for Casting High-Al Steels - Lu, Boxun; Wang, Wanlin (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2015)
With the development of advanced high-strength steel, the slag/steel reaction problems introduced by the addition of aluminum into steel become a challenge for the continuous casting process. An investigation aims to improve the crystallization property of lime–alumina-based mold flux for casting high Al-bearing steels which was carried out through the study of effects of fluorine and BaO on the crystallization behaviors of the mold flux. The single/double hot thermocouple technique and SEM, EDS were employed in the study. The results indicated that the decrease of fluorine content would promote the crystallization behaviors in the lime–alumina-based system which is different to that in the conventional lime–silica-based system, while BaO substituted for CaO can inhibit the crystallization of the lime–alumina-based mold flux. Moreover, the crystallization behavior of mold flux under simulated thermal gradient was in well accordance with TTT results, including the crystallization process and three-layered (liquid, crystalline, glassy) distribution of mold flux.